Three quasi-stellar objects acting as strong gravitational lenses - Courbin, Frédéric; Sluse, Dominique (Astronomy and astrophysics, 2012)
We report the discovery of three new cases of quasi-stellar objects (QSOs) acting as strong gravitational lenses on background emission line galaxies: SDSS J0827+5224 (zQSO = 0.293, zs = 0.412), SDSS J0919+2720 (zQSO = 0.209, zs = 0.558), SDSS J1005+4016 (zQSO = 0.230, zs = 0.441). The selection was carried out using a sample of 22,298 SDSS spectra displaying at least four emission lines at a redshift beyond that of the foreground QSO. The lensing nature is confirmed from Keck imaging and spectroscopy, as well as from HST/WFC3 imaging in the F475W and F814W filters. Two of the QSOs have face-on spiral host galaxies and the third is a QSO+galaxy pair. The velocity dispersion of the host galaxies, inferred from simple lens modeling, is between σ = 210 and 285 km s-1, making these host galaxies comparable in mass with the SLACS sample of early-type strong lenses.